2022
DOI: 10.3390/vaccines10091489
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Knowledge, Attitude, Confidence, and Sociodemographic Factors in COVID-19 Vaccination Adherence among Adolescents in Indonesia: A Nationwide Survey

Abstract: COVID-19 vaccination in adolescents is important because the adolescent population has the highest incidence of COVID-19. This study aimed to explore the factors associated with COVID-19 vaccination adherence among Indonesian adolescents. This cross-sectional study involved 7986 adolescents, polled through online and offline surveys conducted in six major islands of Indonesia. The online questionnaire was distributed through popular social messaging and social media platforms. Our team also contacted schools a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In both cases—child age and parental age—older ages were predictive of the child being vaccinated [ 25 ]. Studies in other settings, including Indonesia [ 26 ] and the United States [ 27 , 28 ] also reported positive associations between age and COVID-19 vaccination coverage within child/adolescent populations.…”
Section: Resultsmentioning
confidence: 95%
“…In both cases—child age and parental age—older ages were predictive of the child being vaccinated [ 25 ]. Studies in other settings, including Indonesia [ 26 ] and the United States [ 27 , 28 ] also reported positive associations between age and COVID-19 vaccination coverage within child/adolescent populations.…”
Section: Resultsmentioning
confidence: 95%
“…Efendi D. et al demonstrated that people with higher levels of knowledge are more likely to adhere to vaccination against SARS-CoV-2. Lack of knowledge about vaccination can lead to misperceptions and misunderstandings of vaccination [ 21 ]. Similar conclusions were reached by Birmingham et al, who demonstrated that people who lacked knowledge about HPV and the HPV vaccine were more likely to be unvaccinated than those who had a greater level of knowledge about the virus [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced by the knowledge score analysis, participants’ knowledge of SARS-CoV-2 is a determining factor in their intention to be vaccinated; in fact, other studies have highlighted that a better knowledge of the COVID-19 vaccine (OR = 1.96; 95% CI = 1.57–2.45) can have a positive impact on vaccine acceptance among young people [ 29 ]. Not understanding the extent of the COVID-19 pandemic led to vaccine hesitancy or refusal [ 10 ].…”
Section: Discussionmentioning
confidence: 99%